Análisis de la deserción en la educación superior: modelo de datos de panel para los departamentos de Colombia, 2014 – 2020 (2023)
Education in Colombia over the years has been affected by low investment in this sector, with respect to public spending, in addition to little investment in technology, which generates low economic growth for the country. One of the main problems that comes with not having the resources, nor the best access to a good education, is dropout. In this work, the behavior of dropout in higher education and its main socioeconomic determinants for the departments of Colombia are analyzed. , during the period from 2014 to 2020. The work begins with a brief analysis of the importance of human capital and its contribution to economic growth.